Bahasa Inggris - Mulyanah, Elis; Andriani, Diyah Iis (BASIS (Bahasa dan Sastra Inggris), 2024)
This study aims to analyze the types and the factors of using positive politeness strategies in the podcast video. The writer used Brown and Levinson's (1987) theory with qualitative methods in analyzing the data. The data source was taken from a podcast video by Grace Helbig and Mamrie Hart on a YouTube channel. The results of this study show that there are 10 various types of positive politeness strategies such as 6 notice attend to hearer, 4 Intensify interest to H, 2 seek agreement, 1 avoid disagreement, 3 presuppose/ raise/assert command ground, 10 include both S and H in the activity, 1 give or ask reason, 1 give gift to H, 1 Joke to put the hearer at ease, and 1 Assert or presuppose Ss knowledge of and concern for H’s wants. On the other hand, the factors found in the analysis are 16 social distance and 14 Payoff. Based on the results of analyzing the data, the most frequently used in the conversation is to Include both S and H in the activity. It appears 10 times in the conversation. Furthermore, their utterances also are influenced by some factors such as payoff and social distance. From 30 utterances, the writer found social distance is the factor that often occurs in the podcast which appears 16 times.